Clinical features of nivolumab-induced Stevens-Johnson syndrome/toxic epidermal necrolysis: retrospective analysis based on case reports - Li, Ronghui; Lei, Haibo; Wang, Chunjiang; Liu, Xiang (Frontiers in Immunology, 2025)
BackgroundStevens – Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) is a life-threatening adverse reaction to nivolumab. This study investigated the clinical features of nivolumab induced SJS/TEN to provide evidence for diagnosis and treatment.MethodsRelevant articles on nivolumab induced SJS/TEN published before December 31, 2024 were collected by searching the database, and then extracting the data for summary analysis.ResultsThirty-one patients were enrolled with a median age of 65 years (range 43, 86). SJS/TEN appear at a median of 5.5 weeks (range, 0.9 108). Bullae/blisters (64.5%), erythema (54.8%), skin rash (54.8%), epidermal detachment (29.0%) and pain (29.0%) were the main skin symptoms. Skin biopsy showed epidermal necrosis (41.9%), keratinocytic necrosis (38.7%), interface dermatitis (29.0%) and inflammatory cell infiltration (45.2%). After stopping nivolumab and receiving treatment, 74.2% of the patients had improvement in skin symptoms, and 22.6% of the patients died of TEN.ConclusionAs a rare immune-related adverse event of nivolumab, SJS/TEN should be closely monitored during the treatment. Nivolumab induced SJS/TEN has a long incubation period, serious clinical symptoms and poor prognosis.